International cross-border migration in the South-East Baltic: factors, structure, consequences - Yemelyanova Larisa (Baltic Region, 2010)
This article presents the results of an integrated research encompassing both the study of migration processes in the South-East Baltic (volume, structure, directions) and the analysis of factors affecting migration mobility of the population as well as the assessment of migration influence on the socioeconomic development of three border territories.